Translocation of protein kinase C isozymes in thrombin-stimulated human platelets. Correlation with 1,2-diacylglycerol levels. - Joseph J. Baldassare; Patricia Henderson; David Burns; Carson R. Loomis; Gary J. Fisher (1992)
Human platelets were found by immunoblot analysis to express protein kinase C (PKC) isozymes alpha, beta, delta, and zeta, but not gamma, epsilon, or eta. Exposure of platelets to thrombin, in the presence of 1 mM calcium, induced increased membrane association of PKC-alpha, -beta, and -zeta, while the subcellular distribution of PKC-delta remained unaltered. Maximal membrane association (2-fold) of PKC-alpha, -beta, and -zeta occurred within 1 min and was sustained for at least 10 min after the addition of thrombin. Similar results were obtained in the presence of the RGDS peptide, which blocks thrombin-induced binding of fibrinogen to its receptor, which indicates that PKC translocation was independent of fibrinogen binding. In the absence of added extracellular calcium, thrombin-induced translocation of PKC-alpha, -beta, and -zeta was transient, reaching a maximum at 1 min and returning to base line by 10 min. In the presence of calcium, thrombin induced a rapid (within 15 s) 8-fold rise in inositol 1,4,5-trisphosphate, which returned to baseline levels within 1 min, and a biphasic increase in sn-1,2-diacylglycerol (DAG), with peaks at 15 s and 2 min, which remained elevated for at least 5 min. Chelation of external calcium abolished the second phase of DAG formation but had no effect on the kinetics or magnitude of the increase in inositol 1,4,5-trisphosphate or the first phase of DAG formation. Two early PKC-dependent functions, serotonin release and 40-kDa protein phosphorylation, were independent of extracellular calcium and sustained DAG. These data demonstrate that in thrombin-stimulated human platelets the duration of the increased PKC membrane association closely parallels that of increased DAG content, and sustained elevations in DAG content and PKC translocation are dependent on extracellular calcium.